The effect of caffeine on sepsis induced cardiovascular dysfunction (Brazilian Journal of Pharmaceutical Sciences, 2024)
Sepsis is characterized by inadequate microvascular tissue perfusion, leading to organ dysfunction and death. Adenosine levels increase during inflammation and tissue hypoxia, potentially influencing cardiovascular parameters through activation of four receptors coupled to the G protein (A 1 , A 2A , A 2B , and A 3 ). Caffeine a non-selective adenosine receptor antagonist and it might prevent the cardiovascular collapse associated with sepsis. This study aimed to assess caffeine effect on sepsis-induced cardiovascular changes in rats. Animals were submitted to cecal ligation and puncture (CLP) to induce sepsis. Two, 8, and 14 hours after the procedure, CLP and sham groups were assigned to receive caffeine (30 mg/kg, s.c.) or vehicle. Twenty-four hours later, biochemical, and hemodynamic parameters were evaluated in addition to survival rate. Sepsis resulted in hypotension, hyporesponsiveness to vasoconstrictors, reduced renal blood flow, and increased blood glucose and lactate levels. Caffeine prevented changes in glycemic levels, but not in the cardiovascular alterations induced by sepsis. Caffeine also shows no discernible impact on markers of organ dysfunction or tissue perfusion. Thus, while caffeine maintained glycemic levels, it did not mitigate sepsis-induced cardiovascular collapse, organ dysfunction, or affect mortality rates. Therefore, caffeine does not provide significant improvements during sepsis.